Synthesis of Two‐Dimensional Covalent Organic Frameworks in Ionic Liquids. Issue 68 (6th November 2019) - Gao, Yanan; Wang, Chang; Hu, Hui; Ge, Rile; Lu, Meihuan; Zhang, Jianqiang; Li, Zhongping; Shao, Pengpeng; Jiang, Donglin
Abstract: Two‐dimensional covalent organic frameworks were synthesized in high yields by polycondensation in nonvolatile ionic liquids. The resulting crystallites are highly porous and exhibit exceptional capability of removing bisphenol A from water. The one reported is a general method to synthesize microporous and mesoporous frameworks, it allows to achieve regular macroscopic shapes, and it is effective in a wide range of reaction temperatures. Abstract : Ionic liquids have been explored as nonvolatile solvents for the synthesis of covalent organic frameworks. These solvents enabled the synthesis of both microporous and mesoporous frameworks with high crystal quality and regular morphology.